(untitled) (PANGEEA, 2025)
The impact that mining activities and capitalization of nonferrous metal ores have on the environmental conditions cannot be addressed sequentially, but only as a whole, thus leading to a system-type approach of the phenomenon. From this perspective, the entire objective reality of a hydrographic basin, taken as a whole, is considered to be a vast system that behaves like an entity and whose dynamics is controlled by the laws that govern the functionality and stability of systems.